Impact of complications on long-term survival after pediatric liver transplantation. (March 2023) - Leonardi, F.; Campana, E.; Pasulo, L.; Stroppa, P.; Casotti, V.; Pinelli, D.; Colledan, M.; D'Antiga, L.; Fagiuoli, S.
Abstract : INTRODUCTION: Pediatric Liver Transplantation (PLT) usually benefits of excellent long-term patient-survival rates. However, data are sparse regarding the impact of post-transplant complications on the quality of life and survival of these patients. Methods: Patients receiving PLT in a single referral Center were retrospectively evaluated. Complications after LT were collected, defined as early- or late- if before or after 3 months post-LT. Patients' follow-up was defined until death or at March 31 st 2022. Results: Between 1997 and 2004, 232 patients underwent PLT; excluding patients with combined transplantation, intra-operative death and incomplete follow-up, 130 patients were regularly followed. Median age at LT was 14.3 months (range 1.0 month-17.7 years). Major indications for LT were Biliary Atresia (59.2%), Alagille syndrome (10%), Metabolic Liver Disease (8.5%) and Hepatoblastoma (4.6%). Median follow-up was 19.2 years. Thirty-one patients underwent liver re-transplantation. At the end of follow-up, 90 patients were alive. Among the remaining 40 patients 13 died within 3 months from LT. Excluding perioperative deaths, patient-survival rates at 1, 5, 10 and 20 years after LT, were 91.7%, 84.3%, 80.2% and 74.4% respectively. At least one vascular complication occurred in 38.5% of patients (20% hepatic artery thrombosis, 74% portal thrombosis), biliary complications in 27.7% (stenosis). Fifty-six patients (43.1%) presented at least one acute rejection episode, sixty-eight patients (52.3%) showed histological signs of chronic rejection at liver biopsy. Twenty-four patients (18.5%) developed a neoplastic pathology during follow-up (71% PTLD). No differences were observed in survival-rates between patients who did or did not develop biliary, late-vascular complications or episodes of acute rejection. Statistically significant differences in survival-rates were found in patients who developed early vascular complication or post-LT tumours. Conclusions: Our study showed that only the onset of early vascular complications (but not late ones) or post-LT neoplastic complications significantly affect long-term survival of pediatric LT patients.